Piano+: An Approach towards a Performance System Used within Free Improvisation. - Lexer, Sebastian (Leonardo Music Journal, 2010)
This article explores the author's strategy for developing a computer performance system designed for free improvisation with acoustic instruments following a nonidiomatic approach. Philosophical considerations on potentiality and personal and social space and research into the psychology of motivation and behavior have inspired and enabled a different approach to integrating technology with improvisation. The technical realization of a parameter space, in particular utilizing contingent behavior emerging from the convergent mapping of a mixture of controller types, has proven effective for the spontaneous creative decision making required to extend the sonic potential of an acoustic piano while minimizing direct computer operation, as applied regularly in practice by the author.